Islamic law of succession : a practical guide to the laws of faraid (2nd edition) - Mohd Salim, Wan Noraini (CLJ Publication, 2014)
The law of succession takes on great prominence in Shariah, with methods of distribution and entitlement prescribed in extensive details. This second edition, while keeping the original work intact, includes discussion on hibah and method of distribution in multiple deaths. The addition is prompted by rapid development in the areas of wealth development and financial and estate planning products introduced by the financial institutions.